Ethical and Responsible Use of Generative Artificial Intelligence by University Students: Design and Validation of an Instrument Using the Expert Competence Coefficient - Colomo-Magaña, Ernesto; Cabero-Almenara, Julio; Ruiz-Palmero, Julio; Palacios-Rodríguez, Antonio (IJERI: International Journal of Educational Research and Innovation, 2026)
The rapid emergence of generative artificial intelligence (GAI) in higher education makes it necessary to guide its use on the basis of ethical principles and responsible practices. The aim of this study was to validate the Questionnaire on Responsible and Ethical Practices in the Academic Use of Artificial Intelligence (CPREUA-IA) for university students. The expert judgement method was employed, with the Expert Competence Coefficient (ECC) used to select evaluators. Of the 154 initial participants, 77 reached the required level of high competence (ECC ≥ 0.8). The results showed positive ratings for the clarity, coherence, and relevance factors across the seven dimensions of the instrument (ethical and moral practices, metacognitive regulation, self-regulation, critical verification, uncertainty management, legal and regulatory use, and ongoing training), with no items requiring elimination. It is concluded that the instrument demonstrates content validity, and that psychometric validation with university students is now required.